PERBANDINGAN CERITA RAKYAT SI KELINGKING (JAMBI DAN BANGKA BELITUNG) - NFN Imelda (Balai Bahasa Provinsi Riau, 2015)
This research is carried out due to the assumption that many folklores have similarities and differences in some different areas. Hence, it is important to compare the similarities and the differences in other to explore the theme, the plot, the story endings, the characters, and the backgrounds of the stories. In this research, the writer chose one of the folklore which titled Si Kelingking that existed in Jambi Province and Riau Province. The result of the research about the comparison of Si Kelingking story shows that there are similarities in intrinsic elements that researched by applying structural approach. Meanwhile, there are differences in characters and backgrounds in the stories for the comparison of the two folklores with the same titles.